Understanding and acceptance of systems engineering in automotive product development - Kolossváry, Tamás; Feszty, Dániel; Filep, Bálint; Dőry, Tibor (Decision Making: Applications in Management and Engineering, 2023)
Systems Engineering (SE) is a new engineering method for many firms in Automotive Product Development that expectedly advances their development processes to meet their stakeholder needs more effectively. Literature suggest that understanding and acceptance are key factors in the implementation, however comprehensive modes for their increase are barely discussed. In this paper, we propose a Participatory Action Research based on multiple research elements to find an effective technique for gaining understanding and acceptance on SE in a validated model environment of automotive industry called Formula SAE. We present practical outcomes at each steps of the implementation process and analyze the effect of improvements in the context of strategy, structure processes.